Case Report: A Pregnant Woman Diagnosed as ALK-Rearrangement Lung Large Cell Neuroendocrine Cancer With Brain Metastasis - Fu, Zaixiang; Zhu, Ganggui; Wang, Liquan; Hu, Shen; Cheng, Lu; Liu, Fuyi (Frontiers in Oncology, 2022)
Concomitant malignant tumors and pregnancy present many difficult questions to both clinicians and patients. Due to no specific guidelines, each aspect of clinical management requires special considerations. This current report presents a rare case of a 38-year-old pregnant woman at gestational age 33 weeks with complaints of weakness of her right limbs for 2 weeks. After successive cesarean section and craniotomy, a diagnosis of lung large cell neuroendocrine carcinoma (LCNEC) metastatic to the brain was eventually made. Next generation sequencing (NGS) showed ALK-EML4 gene fusion. Immediately afterwards she was started on the targeted therapy with the ALK inhibitor alectinib. Ten months later, all known lesions exhibited a rapid regression, and no new brain metastases were found. Consequently, the therapeutic effect was considered as a partial response. Then, we review the previous literature using PubMed on maternal malignant brain tumors diagnosed during pregnancy, or lung LCNEC associated with ALK fusion, or ALK inhibitors treatment among the pregnant women, eventually, and discuss the concerns of dealing with these patients.